Studies on the structural stability of Co2P2O7 under pressure. (May 2018) - Wang, W.P.; Pang, H.; Jin, M.L.; Shen, X.; Yao, Y.; Wang, Y.G.; Li, Y.C.; Li, X.D.; Jin, C.Q.; Yu, R.C.
Abstract: The crystal structural evolution of Co2 P2 O7 was studied by using in situ high pressure angle dispersive x-ray diffraction with synchrotron radiation. The results demonstrate that the α phase of Co2 P2 O7 goes through a partially irreversible structural transformation to β phase under pressure. The pressure is conductive to reduce the longest CoO bond length of the α phase, and then more uniform CoO bonds and regular hexagonal arrangement of CoO6 octahedra of the β phase are favored. According to the Birch-Murnaghan equation, the fitted bulk modulus B0 is 158.1(±5.6) GPa for α phase and 276.5(±6.5) GPa for β phase. Furthermore, the first-principles calculations show that these two phases of Co2 P2 O7 have almost equal total energies, and also have similar band structures and spin-polarized density of states at their ground states. This may be the reason why these two phases of Co2 P2 O7 can coexist in the pressure released state. It is found that the band gap energies decrease with increasing pressure for both phases. Highlights: The α phase of Co2 P2 O7 goes through an irreversible structural transformation to the β phase under pressure. First principles calculations show that these two phases of Co2 P2 O7 have almost equal total energies; they also have similar band structures and spin-polarized density of states in their ground states.